2017
DOI: 10.12691/rpbs-5-2-1
|View full text |Cite
|
Sign up to set email alerts
|

Tulpas and Mental Health: A Study of Non-Traumagenic Plural Experiences

Abstract: Current models of mental health rely heavily on the assumption that only one agent of self exists in every one brain. Deviations from this model of singularity in mind are heavily stigmatized and often considered disordered. This paper opposes this bias by analyzing one form of plurality in consciousness: tulpamancy. Tulpamancy is a collection of meditative techniques used to create and interact with tulpas, which are experienced as fully autonomous and conscious entities within the mind. Research defining the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…Respondents noted that tulpa practice had improved their condition. Similar results were reported from an online survey, including mention of conditions improving because of tulpa and the use of meditation and/or hypnosis (Isler, 2017).…”
Section: Tulpamancysupporting
confidence: 80%
“…Respondents noted that tulpa practice had improved their condition. Similar results were reported from an online survey, including mention of conditions improving because of tulpa and the use of meditation and/or hypnosis (Isler, 2017).…”
Section: Tulpamancysupporting
confidence: 80%
“…In Veissière's (2016) study on so-called "tulpamancers," using meditative techniques to evocate sentient companions that can be seen and heard outside one's own body, 25% identified with Asperger's syndrome/HFA. This result was replicated in a study by Isler (2017), in which 28% of the tulpamancers reported having an autism diagnosis. As a point of comparison, the estimated prevalence of autism in the general population is 1.68% (Baio et al, 2014).…”
Section: Literature Reviewmentioning
confidence: 66%
“…Neuroscience discoveries further support the assertion that the human mind is naturally ‘multiple and discontinuous’ rather than ‘singular and bonded’ (Itzkowitz et al., 2015). The existence of multiple self‐states (configurations or parts) has also commonly been observed within the counselling and psychotherapeutic literature (e.g., Mearns, McLeod, & Thorne, 2013), and this common phenomenon is increasingly being regarded as existing on the same spectrum as those dissociative identity phenomena arising in the clinical setting (see, for instance Isler, 2017; Itzkowitz et al., 2015). For this reason, some clinicians and people with lived experience of dissociative identity question the validity of the term ‘disorder’ (Isler, 2017; Itzkowitz et al., 2015).…”
Section: Background To the Workmentioning
confidence: 86%
“…The existence of multiple self‐states (configurations or parts) has also commonly been observed within the counselling and psychotherapeutic literature (e.g., Mearns, McLeod, & Thorne, 2013), and this common phenomenon is increasingly being regarded as existing on the same spectrum as those dissociative identity phenomena arising in the clinical setting (see, for instance Isler, 2017; Itzkowitz et al., 2015). For this reason, some clinicians and people with lived experience of dissociative identity question the validity of the term ‘disorder’ (Isler, 2017; Itzkowitz et al., 2015). As commonly attested in critiques of the medical model, the term ‘disorder’ focuses on an individual's struggles rather than their strengths and resources; thus adding to their sense of shame and powerlessness.…”
Section: Background To the Workmentioning
confidence: 86%